Communication Skills and Professional Practice: Does It Increase Self-Efficacy in Nurses? - Leal-Costa, César; Tirado González, Sonia; Ramos-Morcillo, Antonio Jesús; Ruzafa-Martínez, María; Díaz Agea, José Luis; van-der Hofstadt Román, Carlos Javier (Frontiers in Psychology, 2020)
The relationship between nurses and their patients is changing significantly, resulting in a patient-focused model. This work aims to contribute new knowledge about the effect of communication skills on perceived self-efficacy of nursing professionals. A cross-sectional descriptive study was conducted with a final sample consisting of 242 nurses. Different instruments that measured communication skills and the general and specific self-efficacy of nursing professionals were utilized. A positive and statistically significant correlation (p < 0.01) between the communication skills and the perceived general and specific self-efficacy was obtained. Nursing professionals who have adequate communication skills feel more confident and more competent, fostering good interpersonal relationships with their patients, and therefore, their perceived general and specific self-efficacy improved as well. Teaching communication skills is important to help nurses cope with a broad range of stressors in their daily interactions with patients, increasing their perceived self-efficacy.